Impaired Hepatic Ketogenesis in Moderately Obese Men With Hypertriglyceridemia. (1st April 2009) - Vega, Gloria Lena; Dunn, Fredrick L.; Grundy, Scott M.
Abstract : Background: Several studies suggest that increased nonesterified fatty acid flux and increased de novo lipogenesis may contribute to hypertriglyceridemia, but few studies have examined fatty acid oxidation as a factor. Rationale: Endogenous hypertriglyceridemia (increased very low density lipoprotein triglyceride) could result from ( a ) re-esterification of excess nonesterified fatty acids entering the liver, ( b ) activation of hepatic lipogenesis, and/or ( c ) defective oxidation of hepatic fatty acids leading to greater triglyceride synthesis. Therefore, this study used plasma levels of 3-hydroxybutyrate as a marker for fatty acid oxidation. The study was carried out in hypertriglyceridemic and normotriglyceridemic subjects under 3 conditions: ( a ) in the fasting state, ( b ) after a fatty meal that should enhance fatty acid oxidation, and (c) after an oxandrolone challenge, which we recently showed increases fatty acid oxidation. Results: In the fasting state, 3-hydroxybutyrate concentrations in hypertriglyceridemic patients were only 53% of levels in normotriglyceridemic subjects. After a fatty meal, moderate increases in 3-hydroxybutyrate were observed, but values for patients with hypertriglceridemia remained 62% of the levels in the normotriglyceridemic group. A similar pattern of response was observed with oxandrolone challenge. There were no significant changes in fasting or postprandial levels of nonesterfified fatty acids, glycerol, or triglycerides before and during the oxandrolone challenge. Conclusion: Patients with endogenous hypertriglyceridemia seem to have a defect in fatty acid oxidation as indicated by reduced levels of 3-hydroxybutyrate. This defect was observed during fasting, postprandially, and during oxandrolone challenge. We propose that this defect contributes to the development of hypertriglyceridemia.